How Do Large Epidemics Redistribute Market Power? Evidence from the 2003 SARS Shock in China - Jiang, Yating; Zhang, Hongsong (The Review of Economics and Statistics, 2026)
Abstract Market power is costly to build and, once established, is typically persistent and difficult to change. This paper investigates the impact of large economic shocks (serious epidemics) on the redistribution of market power in manufacturing industries. Using a model of firms’ dynamic decisions on production, pricing, and inventory holding, we demonstrate the importance of inventory stock and demand uncertainty in understanding market power and propose a new measure of market power. We find that the 2003 SARS shock in China significantly reduced the market power of firms in SARS-impacted areas. This effect is long lasting. SARS also substantially increased the inventory of affected firms, which partially contributed to the redistribution of market power.